ANALISIS POTENSI DAN KELAYAKAN POC SUSU MASTITIS SEBAGAI PENINGKATAN NILAI TAMBAH PETERNAKAN SAPI PERAH: Indonesia - Dana Amalia; Wien Kuntari (Jurnal Agriovet, 2024)
This study aims to evaluate the added value of mastitis milk processed into Liquid Organic Fertilizer (POC) and the feasibility of the business. The methods used include value-added analysis and investment feasibility assessment. The added value achieved is 73.33%, with a profit margin of 72.86%. In terms of market potential, mastitis milk POC shows strong sales potential. The technical aspects also demonstrate feasibility due to structured distribution and market accessibility. Management and legal aspects are favorable, as the company is organized as a PT and holds the necessary farming permits. Social and environmental aspects are positive as well, contributing to community empowerment and minimal pollution. In the financial analysis, the NPV is Rp353,894,009, net B/C is 2.87, gross B/C is 1.05, IRR is 68.37%, and the payback period is 1.7 years. The break-even points for production and revenue are 24,651 units and Rp1,232,528,509, respectively. In conclusion, mastitis milk POC has the potential for realization and is deemed feasible from both financial and non-financial perspectives..